Earthworm and arbuscular mycorrhiza interactions: Strategies to motivate antioxidant responses and improve soil functionality. (1st March 2021) - Wang, Gen; Wang, Li; Ma, Fang; Yang, Dongguang; You, Yongqiang
Abstract: Earthworms and arbuscular mycorrhizal fungi (AMF) act synergistically in the rhizosphere and may increase host plant tolerance to Cd. However, mechanisms by which earthworm-AMF-plant partnerships counteract Cd phytotoxicity are unknown. Thus, we evaluated individual and interactive effects of these soil organisms on photosynthesis, antioxidant capacity, and essential nutrient uptake by Solanum nigrum, as well as on soil quality following Cd exposure (0–120 mg kg −1 ). Decreases in biomass and photosynthetic activity, as well as nutrient imbalances were observed in Cd-stressed plants; however, the addition of AMF and earthworms reversed these effects. Cd exposure increased superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT) activities, whereas inoculation with Rhizophagus intraradices decreased those. Soil enzymatic activity decreased by 15–60% with increasing Cd concentrations. However, Cd-mediated toxicity was partially reversed by soil organisms. Earthworms and AMF ameliorated soil quality based on soil enzyme activity. At 120 mg kg −1 Cd, the urease, catalase, and acid phosphatase activities were 1.6-, 1.4-, and 1.2-fold higher, respectively, in soils co-incubated with earthworms and AMF than in uninoculated soil. Cd inhibited shoot Fe and Ca phytoaccumulation, whereas AMF and earthworms normalized the status of essential elements in plants. Cd detoxification by earthworm-AMF- S. nigrum symbiosis was manifested by increases in plant biomass accumulation (22–117%), chlorophyll content (17–63%), antioxidant levels (SOD 10–18%, POD 9–25%, total polyphenols 17–22%, flavonoids 15–29%, and glutathione 7–61%). It also ameliorated the photosynthetic capacity, and macro- and micronutrient statuses of plants; markedly reduced the levels of malondialdehyde (20–27%), superoxide anion (29–36%), and hydrogen peroxide (19–30%); and upregulated the transcription level of FeSOD . Thus, the combined action of earthworms and AMF feasibly enhances metal tolerance of hyperaccumulating plants and improves the quality of polluted soil. Graphical abstract: Image 1 Highlights: Cd upregulates S. nigrum antioxidant system but R. irregularis attenuated it. Cd accumulation correlated with SOD and POD enzymes in S. nigrum shoots. E. fetida and R. irregularis can lower Cd toxicity via nutrient optimization. Earthworm-AMF-plant integration contributed to restoring quality of polluted soil. Urease and catalase are potential bioindicators of Cd phytoextraction efficiency. Abstract : An earthworm-AMF-hyperaccumulator partnership promoted soil enzyme synthesis and resulted in the highest Cd tolerance and phytoextraction efficacy.